Building careers abroad: Employability perceptions and capital formation of international graduates in Finland - Shannon, Paige (2024)
International graduate employability is a highly discussed topic as more people become internationally educated. Theoretically, the employability perspective of international graduates remains relatively unexplored. To answer calls for additional international graduate employability research and to extend Bourdieu’s theory of capital, capital building and employability of international graduates is studied through the Finnish context using the research question: “How is capital being formed throughout the duration of international graduates’ host country degrees and how does this impact employability in Finland?” This empirical context is of interest because in Finland, there is a need for international graduates to continue working in the country after graduation. Therefore, there is a theoretical and empirical need to understand how international graduates build capital throughout their degrees to aid in their employability.